Pengembangan Media Pembelajaran Kobela untuk Meningkatkan Kesiapan Membaca di PAUD BIN Bengkulu - Apriana, Nepi (AT-TUFULA: Islamic Education Early Chilldhood, 2025)
Problem this research is how to develop Kobela learning media increase the reading readiness of children aged 5-6 years at PAUD BIN Bengkulu? Aim this research is to develop Kobela learning media increase the reading readiness of children aged 5-6 years at PAUD BIN Bengkulu. Research method is Research and Development (R&D). Results state that the Kobela learning media is very valid, practical and effective in learning the fruit subtheme science. Data from research is valid after being validated by validators teams, material experts at 100% the very valid category, design experts at 92% the very valid category, and language experts at 94.5% the very valid category, which means media based learning. Kobela is valid for development, teacher's response Kobela learning media stated that it was very practical with a percentage gain of 88.3% and students posttest scores increased from an average of 1.93 to 4.02 with poor good criteria.Keywords: Reading Readiness; Kobela; Media.